Efektivitas Penggunaan Media Gambar Peristiwa dalam Pembelajaran Menulis Puisi - Ninggi, Fitrya; Damopolii, Muljono; U, M. Shabir; Djafar, Hamsiah (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to determine the effectiveness of event image media and its use in learning poetry writing material for class V students at MIS Jihadul Iman Pota, East Manggarai Regency. This research uses quantitative experimental research with a one-group pre-test post-test research design. The data collection method was observation and tests (pre-test and post-test). The results of descriptive data analysis show that the average reality score for students writing poetry before using event image media (pre-test) is 56.31. Meanwhile, the average reality score for students writing poetry after using event image media (post-test) was 84.73. The inferential data analysis using the N-gain test showed that the percentage value in the high category was 63%, and the low category reached 37%. This shows a difference in the results of students' poetry writing abilities before and after using event image media, as seen from the post-test score, which is greater than the pre-test score. Thus, event image media is suitable for learning poetry writing material.